2018
DOI: 10.1038/s41598-018-20675-9
|View full text |Cite
|
Sign up to set email alerts
|

Toward reliable population estimates of wolves by combining spatial capture-recapture models and non-invasive DNA monitoring

Abstract: Decision-makers in wildlife policy require reliable population size estimates to justify interventions, to build acceptance and support in their decisions and, ultimately, to build trust in managing authorities. Traditional capture-recapture approaches present two main shortcomings, namely, the uncertainty in defining the effective sampling area, and the spatially-induced heterogeneity in encounter probabilities. These limitations are overcome using spatially explicit capture-recapture approaches (SCR). Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 51 publications
4
96
0
Order By: Relevance
“…multi-site dimension of our study allows exploring variability in the density estimates across landscapes. Our study is yet another example of the potential of combining SCR methods and noninvasive sampling techniques to estimate abundance and density for elusive and wide-ranging species, like large carnivores(Alexander et al, 2015;Broekhuis & Gopalaswamy, 2016;Goldberg et al, 2015;López-Bao et al, 2018;Pesenti & Zimmermann, 2013;Stetz et al, 2018).When examining densities across study areas in the French Jura mountains, we found spatial variation between the three counties, with Doubs area having the lowest densities, Ain the highest densities, and Jura intermediate densities. Our density estimates were of similar magnitude to other lynx populations in Europe: 1.47 and 1.38 lynx/100 km 2 in the Northwestern Swiss Alps(Pesenti & Zimmermann, 2013), 0.58 (Štiavnica mountains) and 0.81 individuals/100 km 2 (Velká Fatra National Park) in Slovakia(Kubala et al, 2017) and 0.9 individuals/100 km 2 in the Bavarian Forest National Park in Germany(Weingarth et al, 2012).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…multi-site dimension of our study allows exploring variability in the density estimates across landscapes. Our study is yet another example of the potential of combining SCR methods and noninvasive sampling techniques to estimate abundance and density for elusive and wide-ranging species, like large carnivores(Alexander et al, 2015;Broekhuis & Gopalaswamy, 2016;Goldberg et al, 2015;López-Bao et al, 2018;Pesenti & Zimmermann, 2013;Stetz et al, 2018).When examining densities across study areas in the French Jura mountains, we found spatial variation between the three counties, with Doubs area having the lowest densities, Ain the highest densities, and Jura intermediate densities. Our density estimates were of similar magnitude to other lynx populations in Europe: 1.47 and 1.38 lynx/100 km 2 in the Northwestern Swiss Alps(Pesenti & Zimmermann, 2013), 0.58 (Štiavnica mountains) and 0.81 individuals/100 km 2 (Velká Fatra National Park) in Slovakia(Kubala et al, 2017) and 0.9 individuals/100 km 2 in the Bavarian Forest National Park in Germany(Weingarth et al, 2012).…”
mentioning
confidence: 77%
“…The multi‐site dimension of our study allows exploring variability in the density estimates across landscapes. Our study is yet another example of the potential of combining SCR methods and noninvasive sampling techniques to estimate abundance and density for elusive and wide‐ranging species, like large carnivores (Alexander et al, ; Broekhuis & Gopalaswamy, ; Goldberg et al, ; López‐Bao et al, ; Pesenti & Zimmermann, ; Stetz et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…North American gray wolves (Canis lupus), Mexican gray wolves (C. l. baileyi), and red wolves (C. rufus) are federally endangered in parts of the United States, whereas coyotes (C. latrans) have expanded range and present a number of management challenges in both wildland and urban environments, including hybridization with wolves (Kays et al 2009, Bohling and. Both coyotes and wolves tend to be highly territorial and strategically defecate to mark and communicate territory extents to conspecifics (Rothman and Mech 1979, Gese and Ruff 1997, Barja and List 2014; therefore, collecting scat samples along travel routes or at rendezvous sites has proven effective , Morin et al 2016, Piaggio et al 2016, L opez-Bao et al 2018. Although camera trapping is perhaps the most widely used method for noninvasively detecting wildlife (Foster and Harmsen 2012), the lack of individually unique natural markings (e.g., pelage spotting or striping) on wolves, coyotes, and other canids typically precludes individual identification from photographs.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, noninvasive genetic sampling that capitalizes on the ecological and behavioral characteristics of canids has become an efficient framework for detecting and individually identifying animals. Both coyotes and wolves tend to be highly territorial and strategically defecate to mark and communicate territory extents to conspecifics (Rothman and Mech 1979, Gese and Ruff 1997, Barja and List 2014; therefore, collecting scat samples along travel routes or at rendezvous sites has proven effective , Morin et al 2016, Piaggio et al 2016, L opez-Bao et al 2018). Furthermore, rubbing in odorous materials, such as carcasses of dead wildlife, is a natural behavioral response of canids (Ryon et al 1986, Martin and Farge 1988, Heffernan et al 2007, and collecting hair from lured ground-based rub pads has been used to detect both wolves and coyotes (Ausband et al 2011).…”
Section: Introductionmentioning
confidence: 99%